Philosophical pitfalls in cosmetic surgery: a case of rhinoplasty during adolescence. Issue 2 (1st December 2002) - Hilhorst, M T
Abstract : In the process of deciding to undergo cosmetic surgery for aesthetic reasons, people may err in various ways. Adolescents in particular run the risk of making errors, and both parents and surgeons have special moral responsibilities to avoid disappointments. Parents should face a number of moral issues; if they fail to do so, surgeons have the moral if not legal responsibility, to raise these issues and take a moral stand. In this paper, a number of pitfalls are specified from a philosophical perspective. A request for surgery should not be granted if patients do not meet the standards required for stable decision making and a balanced judgment, and particularly in those cases where patients fail to understand the assumptions—in terms of human values—underlying the surgical intervention. Assessments of competence should go beyond formal conceptions of autonomy, and should, as will be shown, be made on an individual basis. Substantive questions of personal identity and identity formation, within the context of often rapid psychosocial development and emotional turmoil peculiar to adolescents, should be addressed. The key to the moral evaluation of this surgery therefore lies primarily in a patient's life story.